Respuesta :

When subtracting a number from a negative (like question one) the subtraction sign will now be an addition sign.

1.

6-(-7)=13

For question 2, its simple subtraction. If you subtract a negative from positive, it'l be a negative.

2.

-3 - 3= -6

3.

-15 - 23 = -38

Now we combine my previous explanations. Subtracting a negative from a negative will be like adding (like in question 4)

4.

-9 - (-5)= -4

5.

5 - (-15)=20

6.

78-(-17)=95


Extra Info:

When adding a number (doesnt matter if positive or negative) to a negative it will turn into subtraction.

Examples:

6+(-9)=-3

-9+(-9)= -18